Response of Post-Harvest Behavior of Pineapple (Ananas comosus var. Giant Kew) Fruits at Different Storage Conditions - Dhakal, Mira; Pandey, Suprabha; Bhattarai, Shandesh; Ghimire, Dipendra; Subedi, Sujan (Nepal Journal of Science and Technology, 2022)
The present study was carried out to establish the synergistic effect of CoolBot storage and organic and chemical preservatives on pineapple fruit to lengthen the marketable shelf life. The research work was conducted during the period of 17th Mangsir to 28th, Poush 2077 at the laboratory of the National Horticulture Research Center, Khumaltar, Lalitpur. The pineapple fruits var.Giant Kew was set up in an experimental unit in a Completely Randomized Design (CRD) with eight treatments and replicated three times. The treatments were viz., T1= Dipped in 3 mM salicylic acid for 15 min. under CoolBot storage, T2= Dipped in 5 mM salicylic acid for 15 min. under cool bot storage, T3= Coated with aloe Vera gel and T4=controlled treatment under CoolBot storage and T5= Dipped in 3 mM salicylic acid for 15 min. under ambient storage, T6= Dipped in 3 mM salicylic acid for 15 min. under ambient storage T7= Coated with aloe Vera gel under ambient storage and T8= Controlled treatment under ambient storage condition. Each replication of treatment comprises 8 fruits. Changes in Cumulative physiological weight loss % (Cum. PLW%), Vitamin C content (mg/100 gm), Outside and inside Firmness (N/F) of fruit, pH value of juice, and sensory evaluation were observed during the storage period at every 7 days of an interval. The samples at ambient storage conditions (20.5°C and 61.6%) were removed on day 14, and samples at CoolBot storage (10-12°C and 90-92%) were removed on 35 days of storage by observing the sensory evaluation. Thus the study concluded that the synergistic effect of aloe Vera gel coating and Cool Bot storage has been found effective in pineapple fruits to delay internal browning index and extend marketable shelf life from 14 days (ambient storage) to 35 days.